Comparative Study Of The Performance Of Dabex And Anfo Explosives Based On Fragmentation And Its Influence On Blasting Costs - Simamora, Fredho Imanuel; Purwanto, Purwanto (Aceh International Journal of Science and Technology, 2025)
PT. Semen Tonasa conducts blasting using two explosives, Ammonium Nitrate Fuel Oil (ANFO) and Dahana Bulk Emulsion Explosives (DABEX), each with unique specifications that will affect fragmentation quality and blasting costs. This research evaluates the performance of ANFO and DABEX based on fragmentation quality (optimal recovery rate), which will influence blasting cost. It analyzes the best practices for each explosive in different areas. It uses photographic methods to collect fragmentation samples, which will then be analyzed to obtain optimal recovery rates and blasting costs, using rock factor data and deviation of analysis results, the best practice of each explosive can be determined. Based on the result of the analysis, in terms of fragmentation quality, DABEX explosives outperform ANFO with an optimal recovery rate of DABEX reaching 95.6% while ANFO is 89.3%, however, DABEX takes an average of Rp. 4,583 to blast one ton of limestone with a recovery rate of 95.6% while ANFO with a 89.3% recovery rate costs Rp. 3,369. It was found that better fragmentation quality results in lower costs, and vice versa. This is demonstrated by the linear regression analysis, which reveals a very strong negative correlation (R = 0.9819 for DABEX and R = 0.8917) in the relationship between the high level of recovery and the high cost of dismantling one ton of limestone. Both ANFO and DABEX can reach their maximum performance on area B8. Where the optimal recovery rate for DABEX is 95.31% with a cost/ton of Rp 4,622.75, while the optimal recovery for ANFO is 90.16% with a cost/ton of Rp 3,744.62. Meanwhile, the worst performance is predicted to occur on the northern B9 area, with the optimal recovery rate for DABEX is 94.66% with a cost/ton of Rp 4,703.06, while for ANFO the optimal recovery is 89.18% with a cost/ton of Rp 3,785.95